Violette Leduc og Tove Ditlevsens sentimentale scener - Hellberg, Sherilyn Nicolette (K&K - Kultur og Klasse, 2021)
This article considers the place of sentimentality in the reception and authorships of Violette Leduc (1907-1972) and Tove Ditlevsen (1917-1976). I take as point of departure the recent revival of both these authors in their original languages and in translation, in which they, even from feminist perspectives, seem to be evaluated in terms of their capacity for emotional restraint. Through close readings of Ditlevsen’s Ansigterne (The Faces, 1968) and Gift (Dependency, 1971) and Leduc’s Thérèse et Isabelle (1966), La bâtarde (1964) and Ravages (1955), I argue that both authors thematize the relationship between affect and aesthetics in ways which speak not only to the gendered contexts of their respective societies and cultural establishments, but also to contemporary efforts of feminist canon revision within literary studies and popular culture. I am particularly interested in the ways in which the relationship between words, form and feeling is dealt with across these authorships, and suggest that focusing on the authorship – in addition to the work and instead of the author – might open a kind of stage on which we might better understand how these texts render and relate to their various ”anxieties about audience” (Berlant, ”The Female Complaint” 238). The article contributes to existing scholarship on Ditlevsen and Leduc and develops new methods for addressing the relationship between gender and affect in literary criticism and in the ongoing production of literary history.